Prevalence of Helicobacter pylori Genes (CagA, BabA, and HomB) with Stem Cell Markers (LGR5 and CD133) in Severity of Gastric Disease - Safyia Khalid Abdullah; Wasan Abdul-elah Bakir; Mais Ibrahim Alsikafi (Medical Journal of Babylon)
Background: Gastritis is commonly caused by Helicobacter pylori, which colonizes the mucosa of the gastric epithelium in more than half the population worldwide. It adheres to the gastric epithelium, with an important aspect of the pathogenicity of the microorganism facilitating the transport of certain proteins such as CagA, BabA, and Hom into that epithelium. Objective: This study aimed to determine the association between the co-expression of LGR5 and CD133 in patients with gastric diseases and assess the distribution of H. pylori outer membrane genes (CagA, BabA, and HomB) with gastrointestinal disease outcomes. Materials and Methods: For the 140 patients enrolled, H. pylori virulence factors including Cag, BabA, and HomB were detected using Multiplex real-time PCR, while LGR5 and CD133 expressions were determined via immunohistochemistry. Results: The expressions of BabA and HomB had a significant difference with gastric disease such as gastric cancer, gastric metaplasia, and gastritis with and without the colonization of H. pylori, while there was no significant difference of CAG gene expression with gastric disease. Co-expression of LGR5 and CD133 had significant association with gastric disease. Conclusion: There was a significant increase in H. pylori Ag (BabA and HomB) expression among patients with gastric disease. However, no significant differences were observed between H. pylori Cag Ag expression among patients with gastric disease, and all the patients were infected with H. pylori having the Cag gene (100%). It is suggested that CD133 and Lgr5 may play an important role in gastric carcinoma.